Guinea worm: a case study of an eradication programme - Molyneux, CMG, David (Henry Stewart Talks, 2020)
Guinea worm essentials, The certification process, Guinea worm eradication essential interventions and components, Unsafe water source, Innovative approaches including reward, Animal infection, Epidemiology in Chad, Mali, Measuring and documenting surveillance and response